EFFECT OF DATES AND PLANTING DENSITY ON FLOWERING CHARACTERISTICS AND YIELD OF TWO VARIETIES OF STRAWBERRY (Fragaria × ananassa Duch.) - Zuhair A. Dawood (Mesopotamia Journal of Agriculture)
This experiment was conducted in Agricultural Research center of Ainkawa / Erbil / Iraq, during the growing season 2005-2006. The aim of this experiment was to investigate the effect of planting dates and plant density on flowering and yield of two varieties of strawberry (Fragaria× ananassa Duch.) Three planting dates 20 thsep., 10 thoct. And 30 thoct. In 2005 and three plant densities (46000, 23000 and 15332 plants/Hec) with two varieties of strawberry “ Kaiser's samling and Hapil” had been investigated. The annual hill system were used with fixed spacing (1m) between rows. The experimental design was split-split plot within RCBD, with 4 replicated and the experimental unit area was 7.2m2. All results were tested by using Duncan’s multiple range test at probability of 5%. The obtained results could be summarized as following: